Developer's Responsibility Towards Consumers For The Delay In The Submission Of Apartment Unit Ownership Certificates - Yosi Argenta, Aulia; Subekti, Rahayu; Mulyanto, Mulyanto (International Journal of Educational Research & Social Sciences, 2024)
This research aims to explain the developer's default in terms of delays in providing the Flat Ownership Certificate (SHMSRS) and the developer's responsibility to consumers regarding delays in receiving the SHMSRS. The method used in this research is normative juridical. with a statutory approach and a conceptual approach. According to the findings of this study, if the developer is late in providing SHMSRS to consumers, the developer has committed a default. The developer is not timely in carrying out its obligations towards consumers because SHMSRS needs to be obtained as proof of ownership of the apartment unit. The developer's responsibility in the event of delays in providing SHMSRS is to be able to process SHMSRS as quickly as possible and immediately hand it over to consumers. However, consumers can also cancel the purchase of an apartment and the payment received must be returned in full by the developer to the prospective buyer. If the developer cannot comply, consumers can take legal action, namely by mediating and resolving disputes outside the court (Mediation and Arbitration), filing a lawsuit with the General Court (Civil), administrative legal action, submitting a report to the police investigator (criminal action).